2007
DOI: 10.5688/aj710462
|View full text |Cite
|
Sign up to set email alerts
|

Job Turnover Intentions Among Pharmacy Faculty

Abstract: Objectives. To determine the primary reasons why pharmacy faculty intend to remain or leave their current institution and why they left their most recent academic institution, and the relative contribution of various organizational and individual characteristics toward explaining variance in turnover intentions. Methods. A survey instrument was e-mailed to pharmacy faculty members asking respondents to indicate up to 5 reasons for their intentions and up to 5 reasons why they left a previous institution. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 26 publications
3
71
1
Order By: Relevance
“…The results may reflect the worker's own assessment of whether and how her/his work situation and health condition match. In other studies, high turnover intentions have been associated with high workload [55] and job dissatisfaction [56]. Hence, a need for change in the work situation due to too high workload may be a reason for turnover intentions.…”
Section: Discussionmentioning
confidence: 85%
“…The results may reflect the worker's own assessment of whether and how her/his work situation and health condition match. In other studies, high turnover intentions have been associated with high workload [55] and job dissatisfaction [56]. Hence, a need for change in the work situation due to too high workload may be a reason for turnover intentions.…”
Section: Discussionmentioning
confidence: 85%
“…High turnover intentions among employees has been associated with strenuous work conditions, such as high work load [46], low advancement possibilities [47], low skill variety [48], low social support [49], low autonomy and feedback [50,51]. Several studies [42,43] have shown positive effects of mobility from jobs that do not fit the individual's competence or abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to shared expenses, the departments of pharmacy services and pharmacy practice developed an integrated working relationship. Although this proposal did not specifically address the importance of teamwork in leadership, integration of service resources has the potential to help alleviate work-life stressors, an area identified by junior faculty as a concern by other studies (Conklin & Desselle, 2007;Fuller, et al, 2008). Buring, Bhushan, Brazeau, Conway, Hansen, and Westberg (2009) identified faculty leadership development as a necessary skill set rather than another faculty responsibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the pharmacy faculty nationwide, within junior faculty 29% are female and 19% are male, whereas within senior faculty 19% are female while 33% are male. Additionally, organizational features unique to each institution, such as location at a satellite campus, scholarship requirements for promotion, responsibilities secondary to the number of open faculty positions, increased teaching load or clinical responsibilities might contribute to the faculty member's decision to serve as a mentor (Conklin & Desselle, 2007). Fundamental leadership skills are essential to enable faculty to develop new practice sites, while working with an interprofessional team.…”
Section: Introductionmentioning
confidence: 99%